The Influence Of Training, Internal Communication, And Leadership On Personnel Work Discipline Of The Fire And Rescue Department Of Muara Enim Regency - Yuli Sri Susanty; Abdul Basyith; Nisma Aprini (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study aims to determine and analyze the influence of training, internal communication, and leadership, individually and collectively, on work discipline among personnel in the Muara Enim Regency Fire and Rescue Department. The analysis used descriptive and inferential analyses, employing statistical calculations using multiple regression formulas, partial and simultaneous tests, and coefficients of determination. The results showed that training, internal communication, and leadership simultaneously have a positive effect on work discipline among personnel in the Muara Enim Regency Fire and Rescue Department. Training, internal communication, and leadership have a positive effect individually on work discipline among personnel in the Muara Enim Regency Fire and Rescue Department.